Beyond the post‐political: is public participation in Australian cities at a turning point?. (14th September 2018) - Legacy, Crystal; Rogers, Dallas; Cook, Nicole; Ruming, Kristian
Abstract: This special section builds on Planning the Post‐Political City—Part 1 to examine if and how planning is showing signs of a post‐democratic turn taking place in Australian cities. In Part 1, we presented a collection of papers examining Australia as a post‐political landscape, exploring the new ways in which Australian publics are resisting dominant neoliberal practices and logics of growth and, in doing so, are intervening in decision‐making practices to assert new forms of power and participation. In Part 2, we show how participatory practices continue to evolve. We use this brief editorial to ask a foundational question: have those implicated in the governance and management of Australian cities embarked on a post‐democratic path? As they are presented with new exclusionary and managerial governance systems, the public's participation suggests at the very least that post‐political and post‐democratic conditions are neither immutable nor inevitable. However, more democratic forms of governance rely on a rich array of activist types and approaches requiring greater institutional support in order to challenge Australia's post‐political condition.